1993
DOI: 10.1111/j.1530-0277.1993.tb05649.x
|View full text |Cite
|
Sign up to set email alerts
|

Diminution of Biological Reactivity of Ethanol by Changing the Solution Structure by Weak Ultrasonication

Abstract: The weak ultrasonication (40 kHz, 12 mW, 1 week) of ethanol solutions was found to reduce stimulation of the senses of smell and taste by the ethanol on the basis of blind tests with an aqueous ethanol solution (33.0% w/v) and an immature distilled spirit (25.0% v/v). Experiments on mice also demonstrated that a treated aqueous ethanol solution had a weaker depressant effect on the central nervous system, as evaluated by the relative frequency with which mice regained the righting reflex at a dose of either 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…16 Sonication of aqueous ethanol makes it more compact and homogeneous with increased density. 17 Potentized iodine and Cina also show strong absorbance in the UV region. 18,19 Alcohols self-associate via H-bonding resulting in the formation of many different structures such as free units, cyclic dimers, trimers, and tetramers, linear dimers and higher multimers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Sonication of aqueous ethanol makes it more compact and homogeneous with increased density. 17 Potentized iodine and Cina also show strong absorbance in the UV region. 18,19 Alcohols self-associate via H-bonding resulting in the formation of many different structures such as free units, cyclic dimers, trimers, and tetramers, linear dimers and higher multimers.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the number of water molecules in the hydration sphere of sonicated aqueous ethanol is smaller than that in nonsonicated aqueous ethanol. 17 Like Nux v potentized ethanol is also a homeopathic medicine with speci®c therapeutic uses. 26 The variation in chemical shift values in potentized Nux v and ethanol is due to varied shielding effects on 2 H. In linear molecules such as ethanol an important contribution to the total shielding a proton experiences is the result of paramagnetic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Replacing borosilicate glass NMR test tubes [38] with soda glass tubes [39] eliminated previously seen effects. Haseba et al [40] found differences between ultrasonicated and untreated ethanol (in human sensory stimulation, mice rectal temperature and righting reflex regaining time, and NMR T1 times) in samples containing trace elements in the mg/kg range [Haseba T, personal communication, 2003-02-17). One of our investigators (CW) had repeatedly found differences between mother tincture potencies and potentised ABD using a black box device.…”
Section: Discussionmentioning
confidence: 99%
“…The altered T1 values of the deuterium nuclei of Cina 200 and Cina 1000 as compared to those of aqueous tumbling in the relevant parts of the molecule in potentized Cina has undergone a change obviously due to CT interaction and mechanical agitation (Sukul, 1999) . Haseba et al (1993) reported that the thermal motion of water molecules in sonicated aqueous ethanol was greater than that in unsonicated one, and this change in the solution structure produced significant biological effects.…”
Section: Discussionmentioning
confidence: 99%